BESTEIROS DO CONTO (CROSSBOWMEN): Organization, abuses of power and irregularities during the reign of Dom João I (1385-1433) - Ferreira,Leandro Filipe Ribeiro (2014)
The aim of this paper is to examine an aspect of social life linked to one of the most important and original forms of military organization in the whole of Portuguese history-the besteiros do conto (crossbowmen). This research centers mainly on the royal documents issued under the rule of Dom João I, which made it possible to arrive at a series of perspectives illustrating the constant abuses perpetrated inside this militia, with attention being drawn most notably to the municipal offenses directed against the privileges enjoyed by the crossbowmen, the situations in which these men themselves committed abuses, and, finally, the attempts made to legally escape appointment to this military force.